2020
DOI: 10.3389/fimmu.2020.01262
|View full text |Cite
|
Sign up to set email alerts
|

Internalization and Intoxication of Human Macrophages by the Active Subunit of the Aggregatibacter actinomycetemcomitans Cytolethal Distending Toxin Is Dependent Upon Cellugyrin (Synaptogyrin-2)

Abstract: The Aggregatibacter actinomycetemcomitans cytolethal distending toxin (Cdt) is a heterotrimeric AB 2 toxin capable of inducing cell cycle arrest and apoptosis in lymphocytes and other cell types. Recently, we have demonstrated that human macrophages are resistant to Cdt-induced apoptosis but are susceptible to toxininduced pro-inflammatory cytokine response involving activation of the NLRP3 inflammasome. Exposure to Cdt results in binding to the cell surface followed by internalization and translocation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 65 publications
2
23
0
Order By: Relevance
“…Indeed, we have demonstrated that soon after exposure to Cdt, intracellular molecular complexes form that contain both CdtB and cellugyrin. Moreover, cells deficient in the expression of cellugyrin (Jurkat Cg- ) were resistant to CdtB internalization and intoxication ( Boesze-Battaglia et al, 2017 ; Boesze-Battaglia et al, 2020 ). Therefore, we explored whether this dependence on cellugyrin also extended to HdCdt and CjCdt.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, we have demonstrated that soon after exposure to Cdt, intracellular molecular complexes form that contain both CdtB and cellugyrin. Moreover, cells deficient in the expression of cellugyrin (Jurkat Cg- ) were resistant to CdtB internalization and intoxication ( Boesze-Battaglia et al, 2017 ; Boesze-Battaglia et al, 2020 ). Therefore, we explored whether this dependence on cellugyrin also extended to HdCdt and CjCdt.…”
Section: Resultsmentioning
confidence: 99%
“…We have demonstrated previously that shortly after holotoxin binding to human lymphocytes and macrophages, CdtB is internalized via its association with cholesterol rich membrane microdomains ( Boesze-Battaglia et al, 2006 ; Boesze-Battaglia et al, 2009 ; Boesze-Battaglia et al, 2015 ; Boesze-Battaglia et al, 2016 ). Internalization leads to an association of CdtB with cellugyrin, a component of synaptic-like microvesicles (SLMVs) which may participate in intracellular transport ( Boesze-Battaglia et al, 2017 ; Boesze-Battaglia et al, 2020 ). Moreover, reduced expression of cellugyrin protects cells from CdtB internalization and subsequent toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…The following reference appears in the Supplemental Information: Azarnia Tehran et al., 2015 , Boesze-Battaglia et al., 2020 , Buchrieser et al., 2020 , Canton and Kima, 2012 , Harrison et al., 2016 , Kali et al., 2021 , Schnell et al., 2016 , Secher et al., 2015 , Wu et al., 2019 , Wu et al., 2020 , Zilbermintz et al., 2015 .…”
Section: Supporting Citationsmentioning
confidence: 99%
“…CDT is a prominent virulence factor of CDT-producing bacteria and aids in effective tissue colonization, thereby promoting potent infection by breaking down host defense ( 50 ). The dampened host defense mainly results from: (i) disrupted epithelial barrier, which is caused by CDT-induced cell cycle arrest and subsequent cell death in epithelial cells ( 51 ); and (ii) impaired host immunity, which is caused by the extreme sensitivity of lymphocytes to CDT cytotoxicity and altered macrophage functions ( 52 , 53 ). To perform such sophisticated tasks, the CDT must first enter the cells to exert its activity.…”
Section: Bacterial Genotoxins and Their Biological Functionsmentioning
confidence: 99%